Memoir of the Leader of the Khorezm Jadid Movement - Khudayberdiyeva Aynabad Rozimurodovna (Genius Journals, 2023)
Palvanniyaz Yusupov, the leader of the Khorezm Jadid movement and the first chairman of the government of the People's Republic of Khorezm, was born in 1861 in a merchant family. He grew up under the care of his parents until he was 10 years old. Unfortunately, after the death of his parents in 1871, his uncle Yusufboy took him under his care. His uncle, Yusufboy, made it possible for him to study at a school in Khiva and to acquire knowledge of commerce like himself. Palvanniyaz, who loved to trade, traveled with his uncle to Russia in 1877, Iran, Turkey, Egypt, Syria, and Arabia in 1904- 05. After visiting the cities of Mecca and Medina, he returned to Khorezm as Palvaniyazhaji
Keywords: Palvaniyazhaji; knowledge; Khiva; loved